MERANCANG PEMBELAJARAN MENGGUNAKAN PENDEKATAN ADDIE UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS MAHASISWA AGAR MENJADI PUSTAKAWAN YANG BERETIKA - Dewi, Laksmi (Edulib, 2018)
As a profession, a librarian has an ethic codes to be understood by librarian candidates. In the learning process, candidates or students should be introduced to the knowledge, attitude, and skills required to become a librarian. Through the learning process in the Etika Profesi Pustakawan (Professional Etiquette of Librarians) subject, students are introduced to a number of attitudes, ethics, and knowledge, prompting them to think critically in order to become a professional librarian with good etiquette. To achieve such goal, the learning process should be designed in the first place using the ADDIE approach to achieve expected results in accordance with the goals set. The present study is a review on an instructional design which can be developed to improve the quality of learning process, particularly in the efforts to enhance students’ critical thinking skill in order to become an ethical librarian. The development of the learning design employs the ADDIE approach. The ADDIE model consists of Analysis, Design, Development, Implementation, and Evaluation. The Analysis step is purposed to identify potential factors causing a gap in the performance. In the Design step, the expected performance is tested and assessed using proper testing method. The Development step comprises an activity to produce and validating the selected learning resources supporting the learning process. The Implementation step comprises the preparation of learning environment and the involvement of the students. At last, the Evaluation step is done to evaluate the quality of the learning process and products, both before and after the implementation of the program. Through ADDIE model approach, a learning program will be designed, aiming at improving students’ critical thinking ability in order to become an ethical librarian.